FRI0084 Autopsy reports of the cerebrum of 24 patients with sle in the period 1988–99. (1st June 2001) - Allaart, CF; Rood, MJ; Van Duinen, SG; Huizinga, TW
Abstract : Background: Clinical manifestations of neurologic involvement in patients with SLE (Neuropsychiatric SLE or NPSLE) may be either due to secundary causes such as antiphospholipid-syndrome associated infarctions or bleedings or infections, or due to primary causes such as immune-mediated vasculitis or cerebritis. Depending on the probable cause, different therapeutic approaches are chosen. Objectives: Previous reports on histopathologic have suggested that, since it is so seldomly found, cerebral vasculitis cannot be an important cause of neurologic symptoms in SLE. Methods: Results: However, a search in the computer archives of PALGA, the foundation that collects all pathology reports from Dutch PA-laboratories, beginning in 1988 and covering all reports since 1990, revealed vasculitis laesions in no less than 5 of 24 cranial autopsies of patients with SLE. In an additional 4, laesions were described that were compatible with remnants of previous vasculitis. Conclusion: These findings suggest that cerebral vasculitis must be considered as a possible underlying cause of symptoms when it comes to choosing therapy for patients with NPSLE.